Influence of Irradiated Peripheral Blood Mononuclear Cells on Both Ex Vivo Proliferation of Human Natural Killer Cells and Change in Cellular Property - Delso-Vallejo, María; Kollet, Jutta; Koehl, Ulrike; Huppert, Volker (Frontiers in Immunology, 2017)
Clinical studies with adoptive immunotherapy using allogeneic NK cells showed feasibility, but also limitation regarding the transfused absolute cell numbers. First promising results with peripheral blood mononuclear cells (PBMC) as feeder cells to improve the final cell number need further optimization and investigation of the unknown controlling mechanism in the cross-talk to NK cells. We investigated the influence of irradiated autologous PBMCs to boost NK cell proliferation in the presence of OKT3 and IL-2. Our findings demonstrate a requirement for receptor-ligand interactions between feeders and NK cells to produce soluble factors that can sustain NK cell proliferation. Thus, both physical contact between feeder and NK cells, and soluble factors produced in consequence, are required to fully enhance NK cell ex vivo proliferation. This occurred with an indispensable role of the cross-talk between T cells, monocytes and NK cells, while B cells had no further influence in supporting NK cell proliferation under these co-culture conditions. Moreover, gene expression analysis of highly proliferating and non-proliferating NK cells revealed important phenotypic changes on 5-days cultured NK cells. Actively proliferating NK cells have reduced Siglec-7 and 9 expression compared to non-proliferating and resting NK cells (day 0), independently of the presence of feeder cells. Interestingly, proliferating NK cells cultured with feeder cells contained increased frequencies of cells expressing RANKL, B7-H3 and HLA class II molecules, particularly HLA-DR, compared to resting NK cells or expanded with IL-2 only. A subset of HLA-DR expressing NK cells, co-expressing RANKL and B7-H3 corresponded to the most proliferative population under the established co-culture conditions. Our results highlight the importance of the crosstalk between T cells, monocytes, and NK cells in autologous feeder cell-based ex vivo NK cell expansion protocols, and reveal the appearance of a highly proliferative subpopulation of NK cells (HLA-DR/RANKL/B7-H3+) with promising characteristics to extend the therapeutic potential of NK cells.